[Kalendarz podziemny na rok 1985 wydany przez Solidarność Walczącą] . Unofficial calendar for 1985 by Solidarność Walcząca (Agencja Informacyjna Solidarności Walczącej, 1985)
Black and red print on white paper. Calendar includes a portrait of Józef Piłsudski with a laudatory note. Price: 100 zł